Impact of The Use of Chemicals in Salons Around Universitas Negeri Semarang - N., Nisa Trisna; S., Laura Marulia; NR, Nabila Gustin Eka; A., Hany Risna; P., Bellinda Annisa; T., Daniel Bendon (Universitas Negeri Semarang, 2024)
The use of cosmetics containing chemicals must be balanced with the risks that must be accepted, including side effects or other unwanted reactions. Groups that are vulnerable to this usually include those directly involved in using or application, one of which is salon workers. This study will discuss the impact of using chemicals in beauty salons X and Y at Universitas Negeri Semarang and one branch of another beauty salon X at Universitas Muhammadiyah Semarang, with a total of 10 respondents. The study used a survey method with a cross-sectional research design, employing primary data collected by interviews using questionnaires and direct observation. The high level of risk for respiratory disorders and skin irritation, as obtained from data taken from beauty salon X and beauty salon Y, concludes that it is necessary to carry out controls such as labeling the ingredients used in salons, especially chemicals, rotating or shifting employees and the use of Personal Protective Equipment (PPE) for salon employees who are doing treatment. The recommendations that can be given can be applied to various parties, not only to salon employees but also to owners and customers of the beauty salon itself.